PROPOSITION P IS AN INVITATION TO TROUBLE. (Tufts Archival Research Center, 2007)
Marginalia; Draft; Draft of pamphlet against San Francisco's proposed Proposition P. Includes quotes from Hon. Willie Brown, Jr arguing that the proposition will result in harassment, selective enforcement, and discrimination. Urges citizens to vote against proposition. Includes two separate lists of people and organizations opposed to proposition, one for a pamphlet aimed at African-Americans and one for a pamphlet aimed at homosexuals.